Patung Manusia Pada Kubur Kuna Etnis Batak, Sisa-Sisa Budaya Megalit dan Tradisi di Sumatera Utara - Nenggih Susilowati (Balai Arkeologi Sumatera Utara, 2010)
AbstractHuman statue in the ancient graves at Tanah Batak is a symbol of ancestor. Stance is associated with cult and repellent function of disaster. Making a simple style human statues or often called “primitive” describes the continuity of culture or tradition of megalithic. Simple style of the displayed image illustrates the high art of making statues associated with the objectives related to the old region of Batak ethnic.The existence of the human statues that can also be viewed as a form of local wisdom in maintaining the original elements of Batak society.